PEMANFAATAN LIMBAH JAMUR TIRAM SEBAGAI PUPUK ORGANIK PADA BUDIDAYA SELADA (Lactuca sativa L.) - Ida Hodiyah; Fitri Kurniati; Restu Rinda Wijaya; Wawan Setiawan (Jurnal Agroekoteknologi, 2018)
Oyster mushroom growing media generally in the form of sawdust. The sawdust contains high levels of cellulose, hemicellulose and lignin so that the C/N ratio is high. Mixing with manure and composting are one way to improve the quality of compost. The purpose of this study was to determine the effect of oyster mushroom waste combined with fermentation time on lettuce growth. The research method used a randomized block design with treatment namely A=oyster mushroom media waste 100% fermented 20 days, B=oyster mushroom waste 100% fermented 25 days C=75% oyster mushroom waste+25% goat manure fermented 20 days, D=75% oyster mushroom waste+25% goat manure fermented 25 days, E=50% oyster mushroom waste+50% goat manure fermented 20 days, F=50% oyster mushroom waste+50% goat manure fermented 25 days, G=25% oyster mushroom waste+75% goat manure fermented 20 days, H=25% oyster mushroom waste+75% goat manure fermented 25 days each treatment was repeated four times. Parameter observed were leaf area, number of leaves, net assimilation rate, root and wet weight ratio per plant. The results showed that a combination of compost consisting of 25% mushroom waste+75% goat manure both fermented 20 days and 25 days had a good influence on leaf area, leaf number, root fission ratio and weight of wet stover per lettuce plant. Keywords: Compost, Fermentation, Lettuce, Organic fertilizer